Efecto de campos eléctricos y magnéticos sobre algunos sistemas cuánticos confinados de un electrón - Cruz Osorio, Elizabeth (Universidad Autónoma Metropolitana, 2023)
In this work, the effects of electric and magnetic fields in confined quantum systems of one electron were studied by means of the energy spectrum and informational measures, such as Shannon entropy and Fisher information in the configuration space as well as in the momentum space. We started with the study of a free particle confined in a circular region of radius r0 , we obtained the energy eigenvalues. As is well known, the energy levels for states with non-zero angular momentum are doubly degenerate. As measures of localization-delocalization of the particle, we calculated the Shannon entropy and the Fisher information as a function of confinement radius. We study this system in order to compare the results in the absence of fields with those obtained when the confined particle is in the presence of a constant electric or magnetic fields. An electron confined in a circular region in the presence of a constant electric field was studied using the linear variational method. Energy eigenvalues and approximate wave functions were obtained for some states of this system. The wave functions were constructed as a linear combination of the wave functions of the particle confined in a circular region without field. We obtained few position expectation values, the standard deviation, and also calculated few information measures such as Shannon entropy, disequilibrium and Fisher information, as a function of the magnitude of the electric field. We observed that the electric field polarizes the electron density and also breaks the degeneracy of excited states. The uncertainty relations for Shannon entropy and Fisher information were verified, as well as the fulfillment of the generalized Heisenberg uncertainty principle. The next system studied was that of an electron subjected to a two-dimensional harmonic oscillator potential confined in a planar circular region in presence of a constant electric field parallel to one of the diameters. We obtained the energy eigenvalues as a function of the magnitude of the electric field and the size of the circular region. Using the linear variational method, the wave functions of some states of the system were constructed as a linear combination of the wave functions of a particle confined in a circular region of radius r0 subjected to a harmonic oscillator potential. In addition, some entropic measures were calculated as a function of the magnitude of the electric field and confinement radius. As in the previous system, the uncertainty relations corresponding to Shannon entropies and Fisher information are satisfied, as well as compliance with the generalized Heisenberg uncertainty principle. Finally, we obtained the energy eigenvalues and wave functions of some states of an electron confined in a circular region of radius r0 in presence of a constant magnetic field perpendicular to the plane defined by the circular region. This system was studied by applying the linear variational method, diagonalizing the hamiltonian matrix at the base of the particle confined in a circular region of radius r0 . As measures of localization-delocalization we calculated the standard deviation, the Shannon entropy and the Fisher information, as a function of the confinement radius and as a function of the magnitude of the magnetic field.; En este trabajo se estudiaron los efectos de campos eléctricos y magnéticos en sistemas cuánticos confinados de un electrón, mediante el espectro de energía y medidas de la información, como la entropía de Shannon e información de Fisher, tanto en el espacio de configuración, como en el espacio de momentos. Comenzamos con el sistema de una partícula confinada en una región circular de radio r0 , obtuvimos los valores propios de energías. Como es bien conocido, los niveles de energía para los estados con momento angular diferente de cero están doblemente degenerados. Como medidas de localización-deslocalización de la partícula, calculamos la entropía de Shannon y la información de Fisher como función del radio de confinamiento. Estudiamos este sistema con el propósito de comparar los resultados en ausencia de campos con aquellos obtenidos en los que la partícula confinada se encuentra en presencia de un campo eléctrico o magnético constante, según sea el caso. Se estudió el caso de un electrón confinado en una región circular en presencia de un campo eléctrico constante, utilizando el método variacional lineal. Se obtuvieron las energías propias y funciones de onda aproximadas para algunos estados de este sistema. Estas funciones se construyeron como una combinación lineal de las funciones de onda de la partícula confinada en una región circular libre de campo. Obtuvimos algunos valores esperados de la posición, la desviación estándar, y también se calcularon medidas de información como la entropía de Shannon, el desequlibrio y la información de Fisher, como función de la magnitud del campo eléctrico. Observamos que el campo eléctrico polariza la densidad electrónica y además rompe la degeneración de los estados excitados. Se verificaron las relaciones de incertidumbre tanto para la entropía de Shannon como la información de Fisher, así como también se verificó el cumplimiento del principio de incertidumbre de Heisenberg generalizado. El siguiente sistema que se estudió es el de un electrón sujeto a un potencial de oscilador armónico bidimensional confinado en una región circular plana en presencia de un campo eléctrico constante paralelo a uno de los diámetros. Obtuvimos los valores propios de energía como función de la magnitud del campo eléctrico y del tamaño de la región circular. Utilizando el método variacional lineal, las funciones de onda de algunos estados del sistema se construyeron como una combinación lineal de las funciones de onda de una partícula confinada en una región circular de radio r0 y sujeta a un potencial de oscilador armónico. Además se calcularon algunas medidas entrópicas como función de la magnitud del campo eléctrico y radio de confinamiento. Al igual que en el sistema anterior, se satisfacen las relaciones de incertidumbre correspondientes a las entropías de Shannon y a información de Fisher, así como también, se verificó el cumplimiento del principio de incertidumbre de Heisenberg generalizado. Por último, obtuvimos los eigenvalores de energía y funciones de onda de algunos estados de un electrón confinado en una región circular de radio r0 en presencia de un campo magnético constante perpendicular al plano definido por la región circular. Estos resultados se obtuvieron aplicando el método variacional lineal, diagonalizando la matriz hamiltoniana en la base de la partícula confinada en una región circular de radio r0 . Como medidas de localización-deslocalización calculamos la desviación estándar, la entropía de Shannon y la información de Fisher, como función del radio de confinamiento y como función de la magnitud del campo magnético.